Contrastive Analysis of Different Types of Shifts in Persian Translation of The Secret - Maasoum, Seyed Mohammad Hosseini; Davtalab, Hoda (Richtmann Publishing, 2012)
Translation shift is one of the most controversial domains of translation studies. In the present study an attempt wasmade to compare different translators’ use of shifts in a literary text. The selected theoretical framework for the present studywas Vinay and Darbelnet (1995). To achieve this aim, a contrastive analysis was done on The Secret by Rhonda Byrne and itsseveral Persian translations. The results of the study revealed that the translators use different types of shifts for a singlesentence. In many cases, the translators use a combination of different kinds of shift in order to transfer an appropriatemassage.